Maritime convection and fluctuation between Vietnam and China: A data-driven study. (March 2020) - Hu, Zhi-Hua; Liu, Chan-Juan; Chen, Wanting; Wang, You-Gan; Wei, Chen
Abstract: A network is usually embedded in a larger network and interacts with other networks simultaneously, while the networks in network science literature are generally examined independently. The trade values can generally reflect periodical (annual or monthly) flows of cargo types and values between two economies, while the geographical and transportation details cannot be embodied although they are important for national logistics and supply chains. We investigate the vessel flows between two national maritime networks activated by possible implications to trade and shipping investments. The maritime network of flows between China and Vietnam is figured as a typical example under the consideration that the two countries are both typical maritime countries and the development of China is slowing down while Vietnam's economy and trade are booming. Using five years' mutual connectivity data between Vietnam and China, the flow directions and amounts are estimated and examined by network and flow analyzing methods. Maritime convection is introduced to investigate the changing cargo flows that represents supply chains between the two countries. Maritime fluctuation is used to study the strength and tendencies of seaborne trade between the two countries. These two aspects are visualized and conceptualized in the context of China's Belt and Road Initiative. New maritime interconnection facilities and opportunities are then discussed based on the results from this analysis. All methods for developing the networks and metrics of convection and fluctuation are incorporated into a system framework. So, the proposed method can be used for general network relation analysis, especially when the networks are connected by flows. Highlights: Convection is a network of flows between the two networks. Advection and diffusion are two kinds of convection behaviors. Maritime convection represents the changing vessel flows between two countries. Maritime fluctuation represents seaborne trade between the two countries. Networks and metrics are incorporated into a data-driven expert system.